Use of large pieces of printed circuit boards for bioleaching to avoid ‘precipitate contamination problem’ and to simplify overall metal recovery - Adhapure, N.N. (MethodsX, 2014)
Very recently bioleaching has been used for removing metals from electronic waste. Most of the research has been targeted to using pulverized PCBs for bioleaching where precipitate formed during bioleaching contaminates the pulverized PCB sample and making the overall metal recovery process more complicated. In addition to that, such mixing of pulverized sample with precipitate also creates problems for the final separation of non metallic fraction of PCB sample. In the present investigation we attempted the use of large pieces of printed circuit boards instead of pulverized sample for removal of metals. Use of large pieces of PCBs for bioleaching was restricted due to the chemical coating present on PCBs, the problem has been solved by chemical treatment of PCBs prior to bioleaching. In short, • Large pieces of PCB can be used for bioleaching instead of pulverized PCB sample. • Metallic portion on PCBs can be made accessible to bacteria with prior chemical treatment of PCBs. • Complete metal removal obtained on PCB pieces of size 4 cm × 2.5 cm with the exception of solder traces. The final metal free PCBs (non metallic) can be easily recycled and in this way the overall recycling process (metallic and non metallic part) of PCBs becomes simple.